2016
DOI: 10.1177/1757177416669424
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicentre study in intensive care units in five cities from the Kingdom of Saudi Arabia: Impact of the International Nosocomial Infection Control Consortium (INICC) multidimensional approach on rates of central line-associated bloodstream infection

Abstract: Implementing IMA through ISOS was associated with a significant reduction in the CLABSI rate in the ICUs of Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Effective interventions with the INICC multidimensional approach and ISOS were reported in ICUs from Argentina (46.63 vs. 11.10 CLABSIs per 1000 CL-days), showing a 76% reduction, and 57% reduction (incidence density rate: 0.43; 95% confidence interval, 0.34-0.6; P < .001) (Rosenthal et al, 2003); Colombia, showing a 73% CLABSI rate reduction (relative risk, 0.27; 95% confidence interval, 0.14-0.52; P = .002) (Alvarez-Moreno et al, 2016); Mexico (46.3 vs. 19.5 BSIs per 1000 IVD days) showing a 58% reduction (Higuera et al, 2005); Turkey (22.7 to 12.0 CLABSIs per 1000 CL-days), showing a 47% reduction (Leblebicioglu et al, 2013); India (6.4 CLABSIs to 3.9 CLABSIs per 1000 CL-days), showing a 39% reduction (Jaggi et al, 2013); and Saudi Arabia (6.9 to 3.1 per 1000 CL-days) (Al-Abdely et al, 2017). In multicentric studies conducted in adult ICUs (14.5 vs. 9.7 CLABSIs per 1000 CLdays) from 15 countries (Argentina, Turkey, Colombia, India, Mexico, Philippines, Brazil, Peru, El Salvador, Costa Rica, Cuba, Lebanon, Macedonia, Morocco, and Panama), showed a 33% reduction ; in pediatric ICUs from 5 countries (Colombia, India, Mexico, Philippines, and Turkey)(10.7 vs. 5.2 CLABSIs per 1000 CL-days), showed a 51% reduction (Rosenthal et al, 2012), and in NICUs from 4 countries (El Salvador, Mexico, Philippines, and Tunisia) showed a CLABSI rate decrease by 55%, from 21.4 per 1000 CL-days during phase 1 to 9.7 per 1000 CLdays during phase 2 (rate ratio, 0.45 [95% confidence interval, 0.33-0.63]) .…”
Section: Limited-resource Settingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Effective interventions with the INICC multidimensional approach and ISOS were reported in ICUs from Argentina (46.63 vs. 11.10 CLABSIs per 1000 CL-days), showing a 76% reduction, and 57% reduction (incidence density rate: 0.43; 95% confidence interval, 0.34-0.6; P < .001) (Rosenthal et al, 2003); Colombia, showing a 73% CLABSI rate reduction (relative risk, 0.27; 95% confidence interval, 0.14-0.52; P = .002) (Alvarez-Moreno et al, 2016); Mexico (46.3 vs. 19.5 BSIs per 1000 IVD days) showing a 58% reduction (Higuera et al, 2005); Turkey (22.7 to 12.0 CLABSIs per 1000 CL-days), showing a 47% reduction (Leblebicioglu et al, 2013); India (6.4 CLABSIs to 3.9 CLABSIs per 1000 CL-days), showing a 39% reduction (Jaggi et al, 2013); and Saudi Arabia (6.9 to 3.1 per 1000 CL-days) (Al-Abdely et al, 2017). In multicentric studies conducted in adult ICUs (14.5 vs. 9.7 CLABSIs per 1000 CLdays) from 15 countries (Argentina, Turkey, Colombia, India, Mexico, Philippines, Brazil, Peru, El Salvador, Costa Rica, Cuba, Lebanon, Macedonia, Morocco, and Panama), showed a 33% reduction ; in pediatric ICUs from 5 countries (Colombia, India, Mexico, Philippines, and Turkey)(10.7 vs. 5.2 CLABSIs per 1000 CL-days), showed a 51% reduction (Rosenthal et al, 2012), and in NICUs from 4 countries (El Salvador, Mexico, Philippines, and Tunisia) showed a CLABSI rate decrease by 55%, from 21.4 per 1000 CL-days during phase 1 to 9.7 per 1000 CLdays during phase 2 (rate ratio, 0.45 [95% confidence interval, 0.33-0.63]) .…”
Section: Limited-resource Settingsmentioning
confidence: 97%
“…Central lineassociated bloodstream infections (CLABSIs) are common complications encountered with their use, with up to 60% of all hospital-acquired bacteremias/fungemias occurring with a vascular access device (Crnich and Maki, 2001). CLABSIs substantially increase morbidity, mortality, length of hospital stay, and increased hospital costs, both in developed and resource-limited countries (Al-Abdely et al, 2017;Devrim et al, 2016;Ziegler et al, 2014;Tarricone et al, 2010;Higuera et al, 2007;Rosenthal et al, 2003). The CLABSI rates in resource-limited countries are 3-5 times higher than that encountered in high-income settings (Al-Abdely et al, 2017) and 75% of the world's population live in lowto-middle income countries (LMICs) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of published literature on BSIs in Saudi Arabia was highlighted in a recent review [16]. Most recent articles of BSIs in Saudi Arabia focused on device-and central line-associated bloodstream infections [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The DAI rates were as follow: for CLABSI (16.3 versus 6.06), CAUTI (6.75 versus 3.41), and VAP (9.8 versus 1.3) (p < 0.05) (Al-Tawfiq and Abed, 2009). In 2017, a recent prospective multicenter study in five ICUs from five cities of Saudi Arabia revealed a substantial decline (56%) in the rate of CLA-BSI under the impact of the International Nosocomial Infection Control Consortium (INICC) (Al-Abdely et al, 2017b). The same group conducted another prospective surveillance study in 2017 at seven ICUs of five hospitals in five cities of Saudi Arabia, through the implementation of the INICC Multidimensional Approach (IMA), and found a slight drop in the deviceassociated HAI (Al-Abdely et al, 2017a).…”
Section: Most Common Pathogens Isolatedmentioning
confidence: 99%